Pemanfaatan Visualisasi Data Untuk UMKM TKI di PERMAI Malaysia - Priambodo, Bagus; Harwikarya, Harwikarya; Jumaryadi, Yuwan (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
In the contemporary landscape of small businesses, the effective interpretation of data has emerged as a crucial driver for informed decision-making and sustainable growth. The main task of our activity is to explain with delves the benefits of data visualization for small businesses, exploring the transformative potential it holds for enterprises operating on a smaller scale. The essence of data visualization lies in its ability to convert complex data sets into accessible and comprehensible visual representations. Small businesses, often faced with resource constraints, can leverage these visualizations to extract meaningful insights, identify trends, and make strategic decisions that align with their objectives. This exploration encompasses the significance of data visualization tools and techniques tailored for small business contexts. As small businesses navigate the intricacies of their operational environment, this program community services underscores the practical applications of data visualization. It sheds light on how visual representations of financial data, market trends, and customer behaviors can empower small business owners to make timely and well-informed decisions. The aim of this community service activity is to explain data visualization to SMEs who work as migrant workers (TKI) on Penang Island, Malaysia.